Genetic analysis of the orthologous crt and mdr1 genes in Plasmodium malariae from Thailand and Myanmar - Pimpat, Y; Saralamba, N; Boonyuen, U; Pukrittayakamee, S; Nosten, F; Smithuis, F; Day, NPJ; Dondorp, AM; Imwong, M (BioMed Central, 2020)
Background Plasmodium malariae is a widely spread but neglected human malaria parasite, which causes chronic infections. Studies on genetic polymorphisms of anti-malarial drug target genes in P. malariae are limited. Previous reports have shown polymorphisms in the P. malariae dihydrofolate reductase gene associated with pyrimethamine resistance and linked to pyrimethamine drug pressure. This study investigated polymorphisms of the P. malariae homologous genes, chloroquine resistant transporter and multidrug resistant 1, associated with chloroquine and mefloquine resistance in Plasmodium falciparum.